Penyuluhan dan Sosialisasi Dampak Bahaya Pemakaian Narkoba Pada Pelajar Di SMA Swasta APIPSU Medan - Harahap, Faisal Sadat. S.; Setha, Dony; Zaini, Ahmad; Na’im, Khairun; Umaroh, M.Tommy; Rismayanti, Rismayanti; Sabila, Puji Chairu; Sitepu, Karolina (Journal Of Human And Education (JAHE), 2025)
One of the issues that teens deal with is drug usage. Drug abuse continues to increase every year, and based on a National Narcotics Agency (BNN) studyApproximately 90% of drug users are students or college students. Students doing drugs will jeopardise the nation-building process. One of the main causes of students' drug use is their inadequate understanding of the risks associated with drugs. Lectures and education on psychotropics and drug harm laws are two ways to educate people about the risks associated with drugs. Students in high school at Tjut Nyak Dhien University's APIPSU Private High School underwent socialisation and counselling on the dangers and consequences of drug usage. The purpose of this outreach is to increase youth and adolescent awareness of the dangers of drug usage. Parents should better understand the importance of giving proper attention to their child.